2010
DOI: 10.1167/iovs.08-3307
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Podoplanin and Other Lymphatic Markers in the Human Anterior Eye Segment

Abstract: Coexpression of Pdpn and Ccl21 at the anterior iris surface and in the chamber angle suggests the constitution of a chemokine gradient guiding APCs through the anterior chamber. The more pronounced expression of Pdpn in the TM could favor egression of APCs by way of the conventional outflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
37
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 69 publications
9
37
2
3
Order By: Relevance
“…Podoplanin is expressed in the trabecular meshwork (reddish staining) but not in Schlemm's canal (arrow) (C; D2-40; 40Â). trabecular meshwork, podoplanin labeling e except for Schlemm's canal e has also previously been reported and is in accordance with our findings (Birke et al, 2010;Hamanaka et al, 2011;Watanabe et al, 2010). Since the podoplanin immunoreactivity in the trabecular meshwork was present in fetal eyes from the 12th WoG and increased with fetal age, we therefore hypothesize that the corneal endothelial staining reaction in fetal eyes younger than 19 WoG may be linked to the immunoreactivity of the trabecular meshwork as both cell types develop from the neural crest during the seventh week of gestation (Barishak, 2001).…”
Section: Expression Of Podoplanin In Our Cohort In Comparison With Thsupporting
confidence: 94%
See 1 more Smart Citation
“…Podoplanin is expressed in the trabecular meshwork (reddish staining) but not in Schlemm's canal (arrow) (C; D2-40; 40Â). trabecular meshwork, podoplanin labeling e except for Schlemm's canal e has also previously been reported and is in accordance with our findings (Birke et al, 2010;Hamanaka et al, 2011;Watanabe et al, 2010). Since the podoplanin immunoreactivity in the trabecular meshwork was present in fetal eyes from the 12th WoG and increased with fetal age, we therefore hypothesize that the corneal endothelial staining reaction in fetal eyes younger than 19 WoG may be linked to the immunoreactivity of the trabecular meshwork as both cell types develop from the neural crest during the seventh week of gestation (Barishak, 2001).…”
Section: Expression Of Podoplanin In Our Cohort In Comparison With Thsupporting
confidence: 94%
“…Podoplanin was also detected in the basal layers of the corneal epithelium and to a lesser degree in keratocytes and the corneal endothelium (Cursiefen et al, 2002). Furthermore, it was found in the trabecular meshwork of healthy donor eyes and glaucoma patients as well as in the iris of human donor eyes (Birke et al, 2010;Hamanaka et al, 2011;Watanabe et al, 2010). Its expression was also demonstrated in lymphatic vessels of the dura mater surrounding the optic nerve and in a nonvascular pattern in the arachnoid mater .…”
Section: Expression Of Podoplanin In Human Eyesmentioning
confidence: 90%
“…27 Given the notion that the globe is devoid of lymphatic vessels 30 and a mature population of lymphocytes, 45 it seems that intraocular lymphoma should be considered stage 5 disease. However, results of recent studies 32,33 suggest that lymphatic vessels exist in the anterior aspect of the uvea of clinically normal sheep and humans. Thus, although the absence of a mature population of lymphocytes in eyes precludes its classification as a secondary lymphoid organ, the presence of lymphatic vessels may indicate eyes are a tertiary lymphoid organ; this would indicate intraocular lymphoma should be classified as stage 1 disease for species with uveal lymphatic vessels.…”
Section: Discussionmentioning
confidence: 99%
“…30 Thus, intraocular lymphomas likely should be classified as stage 5 tumors on the basis of World Health Organization guidelines. However, results of recent studies of sheep 31 and humans 32,33 indicate uveal tissue may have lymphatic channels, suggesting that a revision of this classification scheme may be necessary to improve determination of a prognosis for patients with lymphoma at only an ocular site. To the authors' knowledge, only reports of single cats or dogs with PSOL have been published.…”
mentioning
confidence: 99%
“…D240 (podoplanin) expression in TM cells has been previously reported. 19,30 D240 is a good marker for detecting the disappearance of TM cells in PACG eyes. 18 In this study, we also found that immunohistochemical staining for D240 provided excellent evidence that indicated that TM cells were absent and present in MYOC POAG and non-MYOC POAG patients, respectively.…”
Section: Discussionmentioning
confidence: 99%